THE EVOLUTION OF TECHNOLOGY ACCEPTANCE MODEL (TAM) AND RECENT PROGRESS ON TECHNOLOGY ACCEPTANCE RESEARCH IN ELT: STATE OF THE ART ARTICLE - Dwiyana Putra, I Dewa Gede Rat (Yavana Bhasha : Journal of English Language Education, 2018)
The vast development of Information and Communication Technology (ICT)improves the integration of technology for the academic purpose. This phenomenon thenraises an issue of technology acceptance, which becomes an interesting field of investigationfor many scholars. In this respect, Technology Acceptance Model (TAM) has proven to be arobust, powerful, and parsimonious framework for predicting user acceptance oftechnology integration in various fields (Lai, 2017; Rondan-Cataluna et al., 2015). Althoughthere is a lot of research studies reported the use of TAM and its developed versions ininvestigating the technology acceptance in the educational field, there is no publication thattrying to map current studies which focus on educational technology acceptance researchespecially in ELT. Based on the needs of providing such information, this article wouldpresent the state of the art of the current research trends on the application of TAMframework in investigating ICT integration acceptance in ELT. The main part of this articlewould describe the evolution of TAM framework, followed by the discussion of recentresearch results concerning the technology acceptance, and the future trends of technologyacceptance research in ELT. This state of the art article is expected to inspire other researchersto conduct further studies on technology acceptance in ELT and also suggest the ELTpractitioners about the current and future trends in technology integration for academicpurpose.